Southern Ocean eddy phenomenology - Frenger, Ivy; Münnich, Matthias; id_orcid:0 000-0003-3292-2934; Gruber, Nicolas; id_orcid:0 000-0002-2085-2310; Knutti, Reto (Journal of Geophysical Research: Oceans, 2015)
ISSN:0148-0227 ISSN:2169-9275